2001
DOI: 10.1002/j.2161-0045.2001.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Client Psychological Distress: An Important Factor in Career Counseling

Abstract: The authors explored client psychological distress as a variable in career counseling. Perry-two clients in a naturalistic setting were seen for a total of 290 sessions by 21 counselors-in-training. The results indicated that (a) 60% of the clients were psychologically distressed, (b) clients' scores decreased significantly from pretest to posttest on psychological distress variables, (c) significant linear growth occurred in the clients' perception of the working alliance across sessions, and (d) the psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 22 publications
5
79
0
4
Order By: Relevance
“…Researchers have also used the working alliance as an instrument in the exploration of the process in career counseling (Heppner & Hendricks, 1995;Multon, Heppner, Gysbers, Zook, & Ellis-Kalton, 2001). In general it was found that clients consider the relationship in career counseling as highly important and that the working alliance was developing over time in sessions.…”
mentioning
confidence: 97%
“…Researchers have also used the working alliance as an instrument in the exploration of the process in career counseling (Heppner & Hendricks, 1995;Multon, Heppner, Gysbers, Zook, & Ellis-Kalton, 2001). In general it was found that clients consider the relationship in career counseling as highly important and that the working alliance was developing over time in sessions.…”
mentioning
confidence: 97%
“…Although a review of studies focused on four-year colleges (Gerdes, & Mallinckrodt, 1994;Kahn, Nauta, Gailbreath, Tipps, & Chartrand, 2002;Korschgen & Hageseth, 1997;Leonard, 2002;Lewallen, 1993;Sullivan & Mahalik, 2000) indicated that an effective process aimed at helping undecided students from a practical and emotional perspective is lacking, the research on incoming undecided community college freshmen is sparse. Multon, Heppner, Gysbers, Zook & Ellis-Kalton (2001), however, found that, like their undergraduate college counterparts, community college students typically experienced varying degrees of anxiety when requesting career-counseling assistance.…”
Section: Research On Undecided Students' Negative Thinking Patternsmentioning
confidence: 94%
“…Counselors and advisors should also track these undecided community college freshmen as they experience and become acclimated to the culture of the community college. Multon, Heppner, Gysbers, Zook, & Ellis-Kalton (2001), found that college students typically experienced varying degrees of anxiety when requesting career-counseling assistance.…”
Section: Implications Of Findingsmentioning
confidence: 98%
“…However, choosing one's future career path can be a difficult and stressful process, due to the very large number of possibilities that are open to young adults and the many considerations that need to be taken into account (Multon, Heppner, Gysbers, Zook, & Ellis-Kalton, 2001;324-335;Sauermann, 2005;273-303). Therefore, it is not surprising that young adults are concerned about their future careers and that many encounter difficulties in making this decision (Gati, Krausz, & Osipow, 2012;510-526;Nurmi, 2000;1-15).…”
Section: Career Choicementioning
confidence: 99%